Increased Dendritic Branching of and Reduced δ-GABAA Receptor Expression on Parvalbumin-Positive Interneurons Increase Inhibitory Currents and Reduce Synaptic Plasticity at Puberty in Female Mouse CA1 Hippocampus - Shen, Hui; Kenney, Lindsay; Smith, Sheryl S. (Frontiers in Cellular Neuroscience, 2020)
Parvalbumin positive (PV+) interneurons play a pivotal role in cognition and are known to be regulated developmentally and by ovarian hormones. The onset of puberty represents the end of a period of optimal learning when impairments in synaptic plasticity are observed in CA1 hippocampus of female mice. Therefore, we tested whether the synaptic inhibitory current generated by PV+ interneurons is increased at puberty and contributes to these deficits in synaptic plasticity. To this end, the spontaneous inhibitory post-synaptic current (sIPSC) was recorded using whole cell patch clamp techniques from CA1 pyramidal cells in the hippocampal slice before (PND 28-32) and after the onset of puberty in female mice (~PND 35-44, assessed by vaginal opening). sIPSC frequency and amplitude were significantly increased at puberty, but these measures were reduced by 1 μM DAMGO (1 μM, [D-Ala2, N-MePhe4, Gly-ol]-enkephalin), which silences PV+ activity via μ-opioid receptor targets. At puberty, dendritic branching of PV+ interneurons in GAD67-GFP mice was increased, while expression of the δ subunit of the GABAA receptor (GABAR) on these interneurons decreased. Both frequency and amplitude of sIPSCs were significantly increased in pre-pubertal mice with reduced δ expression, suggesting a possible mechanism. Theta burst induction of long-term potentiation (LTP), an in vitro model of learning, is impaired at puberty but was restored to optimal levels by DAMGO administration, implicating inhibition via PV+ interneurons as one cause. Administration of the neurosteroid/stress steroid THP (30 nM, 3α-OH, 5α-pregnan-20-one) had no effect on sIPSCs. These findings suggest that phasic inhibition generated by PV+ interneurons is increased at puberty when it contributes to impairments in synaptic plasticity. These results may have relevance for the changes in cognitive function reported during early adolescence.